Unemployed Nursing graduates: choice of course and perception of teaching (Research, Society and Development, 2020)
Objective: To verify the reasons for choosing nursing education and the opinion of nurses on the quality of education offered to them, while in the situation of unemployment as a nurse. Methods: This is a qualitative, descriptive, cross-sectional study, conducted with fourteen nurses. Data collection took place through interviews, with a semi-structured questionnaire prepared by the researchers. Data analysis with Content Analysis. Results: The interviewees declared themselves to be white or brown, mostly Catholic, single, without children, aged between 23 and 34 years old, graduated less than two years ago. The choice of Nursing as a profession was justified by reports about having taken high school courses in the area, wanting to help people and being close to the patient. Most of the participants negatively evaluated their training, reporting failures in aspects of coordination and teaching, deprivation of internship field and feeling of lack of professional preparation. Conclusion: The perception of undergraduate nursing by the graduates revealed important points to be improved, where harsh criticisms were observed, including flaws in aspects of coordination and teaching, deprivation of internship field and feeling of lack of professional preparation.